KOMPARASI FUNGSI HASH MD5 dan SHA FAMILY PADA IMPLEMENTASI BLOOM FILTER - Sediyono, Agung (TEKNOINFO, 2007)
The bloom filter is a compact data structure that can be applied as a table look up. It uses a hash and modulo function to convert the string into the bit position of bloom filters. The bloom filter has a false positive weakness because of the impairment of hash function and limitation of bloom size. Therefore, it is important to choose the best hash function so that the false positive rate minimum. This research compares hash function: SHA family and MD5 and chooses which one outperform based on the minimum of false positive rate.